Quantitative Trait Loci Mapping for Plant Height in Tobacco using Linkage and Association Mapping Methods. Issue 2 (1st March 2015) - Cheng, Lirui; Yang, Aiguo; Jiang, Caihong; Ren, Min; Zhang, Yu; Feng, Quanfu; Wang, Shaomei; Guan, Yongsheng; Luo, Chenggang
ABSTRACT: Plant height (PH) is one of the most important agronomic traits in tobacco ( Nicotiana tabacum L.). To gain a better understanding of its genetic basis, the F2 and F2:3 populations derived from NC82 (P1 ) and Kang88 (P2 ) cross were developed. The 193 F2 individuals and 145 F2:3 lines were further used to identify quantitative trait loci (QTL) affecting to PH in tobacco. Two main quantitative trait loci (M‐QTL), designated qPH‐6 and qPH‐12, were mapped on genetic linkage groups 6 and 12, respectively, using linkage mapping (LM). The QTL qPH‐12 was identified as stably expressed in different tobacco generations as well as in various environments. To further verify the chromosomal interval harboring qPH‐12, a total of 96 accessions were subsequently evaluated for PH at two different sites and genotyped by 46 markers evenly distributed on chromosome 12. We found a total of four significant marker‐trait associations that were identified with three different SSR markers ( P < 0.01) and could explain 11.7 to 14.8% of the phenotypic variation in PH. One marker, PT55174, showed a significant association with PH ( P < 0.01) and explained 13.9 and 14.4% of the phenotypic variation at two different sites. Taken together, our results could provide a new avenue for investigating the QTL in tobacco by combining LM and association mapping (AM), and facilitating our understanding of the inheritance of PH for marker‐assisted selection (MAS) in tobacco.